Systematic Literature Review Keparahan dan Jenis Gangguan Suara Pada Pasien dengan Laringitis Akut dan Kronik - Junaeni; Hikmatun Sadiah (Jurnal Terapi Wicara, 2025)
Background: Laryngitis, both acute and chronic, represents a major cause of dysphonia that significantly affects vocal function and quality of life. The differentiation of clinical characteristics, severity, and typology between acute and chronic forms remains an important issue in clinical and speech-language pathology research. Objective: This study aimed to comprehensively analyze the literature on the severity and types of voice disorders in patients with acute and chronic laryngitis, as well as their implications for quality of life. Methods: A qualitative synthesis of approximately 200 studies (2015–2025) was conducted using data from SciSpace, PubMed, and Google Scholar. Inclusion criteria comprised studies employing perceptual and acoustic severity measures (GRBAS, DSI, videostroboscopy) and validated quality of life instruments (VHI, V-RQOL). Data were compared across populations, assessment tools, and laryngitis types. Results: Over 30 studies employing perceptual and acoustic tools consistently demonstrated differentiation between acute and chronic laryngitis. Organic dysphonias showed higher objective and subjective severity scores than functional types. Chronic laryngitis was subdivided into catarrhal, hypertrophic, atrophic, and polypoid forms, frequently associated with benign vocal fold lesions such as nodules and polyps. Quality-of-life studies revealed significant impairments in physical, emotional, and social domains, especially among professional voice users and elderly populations. Dysphonia severity correlated with reduced quality of life, greater social anxiety, and depressive symptoms. Conclusion: Acute and chronic laryngitis produce distinct patterns of voice disorder severity and psychosocial burden. Multimodal evaluation integrating clinical, acoustic, and patient-reported outcomes is essential for effective vocal rehabilitation planning. These findings highlight the need for comprehensive and sustained management approaches for individuals with laryngitis-related voice disorders.